The art of alchemy in siddha's perspective - a study - Muhunthan, S. (Eastern University, Sri Lanka & Sri Sathya Sai University, 2023)
The art of alchemy is generally known in the Hindu tradition as the fourth, out of the sixty-four varieties of fine arts. The term alchemy generally refers to the process of converting iron to gold, yet its true character is basically concerned with healing techniques, medicines to the body, and the solution to incurable diseases. Apart from these, alchemy is also performed for spiritual purposes. Alchemy is known at two stages, viz: Reproducing gold out of metals of lesser value such as lead capper, silver and iron, and also for converting mercury into spatikam (Rasamani / Rasakkattu). At the preparatory stage, alchemy is generally classified into- Nathavethai alchemy, magnetic alchemy, and metallic alchemy. It is totally wrong to presuppose that the gold obtained through alchemy is basically of good metallic value. In fact, the terms 'Gold' and 'Iron' are just symbolic terms used by Siddhas to denote Kalpa (healthy) body and the ordinary human body respectively. Besides, Rasakkattu is an indication of dwelling within the supreme power. Mercury, which is supposed to be the sperm of the supreme power, pressed and calcinated can be used to produce several rare medicines such as Rasapadanga, Rasapaspam and Rasasenthuram. Mercury possessing such rare medical qualities, if worn as a sacred bead in an amulet, is of extreme benefit to humans as held in the Siddha tradition. This is also known as Rasamani Subtlety.There are also other beliefs to the effect that such a Rasamani amulet brings the triple defects to equilibrium, while more semen is produced during a sexual intercourse and gagana siddhi is attained in Kundalini yoga. Thus, the traditional science of the Siddhas acts not only on metals but also on the soul and body of the human being. Just like converting low-quality metals into those of high quality, the Siddhas have tried to convert a diseased struck body into a healthy body. In this regard, the Siddhas have even indicated yoga practice as spiritual alchemy. In the Hindu cultural heritage, gold is indicating a never aging quality and a characteristic of long age. Mercury is an indication of immortality or deathless nature. It can therefore be said that the Siddhas, through alchemy, were only trying to establish eternity through the art of alchemy.
Keywords: Siddha Tradition; Alchemy; Rasamani